Pengaruh Penerapan Model Pembelajaran Think Pair Share Terhadap Hasil Belajar Siswa - Sulfiana Sulfiana; Muhammad Yani; Emmi Azis (Mathematics Education Study Program, 2025)
This research aims to determine the effect of implementing the think pair share learning model on student learning outcomes. The type of research used is experimental research with a quantitative approach. The data processed are the results of the pre-test and post-test given to all class XI IPS students at SMA Negeri 28 Bone. The data collection method in this research is a test instrument. The data was processed using instrument tests in the form of question difficulty level tests and question distinguishing power tests and to answer the research hypothesis descriptive statistical tests and inferential statistical tests were carried out using normality tests and hypothesis tests. Based on the research results and existing data, researchers can conclude that the think pair share learning model has a significant effect on student learning outcomes. This is proven by the increase in the average score from pretest to posttest as well as the results of the hypothesis test that has been carried out, the results of the paired samples test show a sig value (2-tailed) of 0.000 < 0.05, the analysis results of tcount > ttable or 15,000 > 1.74588, so H1 is accepted and H0 is rejected.